Imaging of Neuronal Activity in Awake Mice by Measurements of Flavoprotein Autofluorescence Corrected for Cerebral Blood Flow - Takahashi, Manami; Urushihata, Takuya; Takuwa, Hiroyuki; Sakata, Kazumi; Takado, Yuhei; Shimizu, Eiji; Suhara, Tetsuya; Higuchi, Makoto; Ito, Hiroshi (Frontiers in Neuroscience, 2018)
Green fluorescence imaging (eg., flavoprotein autofluorescence imaging) can be used to measure neuronal activity and oxygen metabolism in living brains without expressing fluorescence proteins. It is useful for understanding the mechanism of various brain functions and their abnormalities in age-related brain diseases. However, hemoglobin in cerebral blood vessels absorbs green fluorescence, hampering accurate assessments of brain function in animal models with cerebral blood vessel dysfunctions and subsequent cerebral blood flow alterations. In the present study, we developed a new method to correct flavoprotein autofluorescence imaging signals for hemoglobin-dependent green fluorescence reductions by simultaneous measurements of green fluorescence and intrinsic optical signals. Intrinsic optical imaging enabled evaluations of light absorption and scatters by hemoglobin, which could then be applied to corrections of green fluorescence intensities. Using this method, enhanced flavoprotein autofluorescence by sensory stimuli was successfully detected in the brains of awake mice, despite increases of cerebral blood flow and hemoglobin interference. Moreover, flavoprotein autofluorescence could be properly quantified in a resting state and during sensory stimulation by a CO2 inhalation challenge, which modified vascular responses without overtly affecting neuronal activities. The flavoprotein autofluorescence signal data obtained here were in good agreement with the previous findings from a condition with drug-induced blockade of cerebral vasodilation, justifying the current assaying methodology. Application of this technology to studies on animal models of brain diseases with possible changes of cerebral blood flow, including age-related neurological disorders, would provide better understanding of the mechanisms of neurovascular coupling in pathological circumstances.